Clinical, histopathological and immunohistochemical features of a thymoma in a domestic rabbit (Oryctolagus cuniculus) – Case report - Almeida, Isabella O.; Alves, Rebeca R.; Gorza, Leonardo L.; Cassali, Geovanni D.; Flecher, Mayra C.; Horta, Rodrigo S. (Brazilian Journal of Veterinary Pathology, 2020)
Thymoma is a neoplasm originating from epithelial cells of the thymus. It represents the most common tumor in the mediastinal region of rabbits, followed by lymphoma. This study aims to report a case of post mortem diagnosis of thymoma in a rabbit (Oryctolagus cuniculus), with the purpose to contribute to the understanding of this disease and its diagnosis in this specie. A six-year-old male mixed breed pet rabbit (O. cuniculus), weighing 2.3 kg, was referred to necropsy exam. The previous clinical history included prostration, lethargy, weight loss, dysorexia and respiratory distress, evidenced mainly on the expiratory phase. Radiographs revealed pleural effusion and the presence of a mass involving the cranial and middle mediastinum, confirmed by ultrasound. In the cytological examination, it was diagnosed as a low-grade lymphoma and chemotherapy was performed with COP (cyclophosphamide, vincristine – Oncovin®, prednisolone). However, after 145 days, euthanasia was performed. At necropsy, a well delimited mass was observed in the mediastinal region, adhered to the pleura, with firm consistency and pale coloration. Histopathological analysis of the mass showed the proliferation of epithelial neoplastics cells, arranged in trabeculas and with infiltration of small lymphocytes. The immunohistochemical findings included cytoplasmic immunolabeling for cytokeratin AE1/AE3 in 90% of epithelial neoplastics cells, while CD3 was evidenced in a small number of lymphocytes (T-lymphocytes) and CD79a in B-lymphocytes localized on the neoplasia periphery. The growth fraction was estimated at 30% by Ki-67. According to the histopathological criteria for thymoma classification proposed by the World Health Organization, 2015, it was made the diagnosis of lymphocyte-rich predominantly cortical thymoma (B1 type).